2013
DOI: 10.1002/jor.22478
|View full text |Cite
|
Sign up to set email alerts
|

DXA and pQCT predict pertrochanteric and not femoral neck fracture load in a human side‐impact fracture model

Abstract: The validity of dual energy X-ray absorptiometry (DXA) and peripheral quantitative computed tomography (pQCT) measurements as predictors of pertrochanteric and femoral neck fracture loads was compared in an experimental simulation of a fall on the greater trochanter. 65 proximal femora were harvested from patients at autopsy. All specimens were scanned with use of DXA for areal bone mineral density and pQCT for volumetric densities at selected sites of the proximal femur. A three-point bending test simulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…That may be the reason, there were no cases of lag screw cut out and 2 cases of z-effect (figure 7) due to varus reduction which was determined in follow up by analysing post-op x-ray showing neck shaft angle <150 degree and severe osteoporotic bone but there was no case of reverse z-effect in our follow up patients. Bone mineral density (BMD) of the trochanteric region obtained in DEXA scan is the best indicator for predicting pertrochanteric fractures [28] . The highest concentration of stress is usually at the lag screw hole of the intramedullary implant [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That may be the reason, there were no cases of lag screw cut out and 2 cases of z-effect (figure 7) due to varus reduction which was determined in follow up by analysing post-op x-ray showing neck shaft angle <150 degree and severe osteoporotic bone but there was no case of reverse z-effect in our follow up patients. Bone mineral density (BMD) of the trochanteric region obtained in DEXA scan is the best indicator for predicting pertrochanteric fractures [28] . The highest concentration of stress is usually at the lag screw hole of the intramedullary implant [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Bone mineral density (BMD) of the trochanteric region obtained in DEXA scan is the best indicator for predicting pertrochanteric fractures [28] . The highest concentration of stress is usually at the lag screw hole of the intramedullary implant [28] . The angle of insertion of a nail during surgery is a very important factor because stress on nail and bone distal to tip of nail depends on the angle of insertion [29] .…”
Section: Discussionmentioning
confidence: 99%
“…It would be wonderful if one could identify a particular group of elderly patients who were vulnerable to sustain fragility fractures around the hip. It has been shown that bone mineral densitometry (BMD) of the trochanteric region of femur, obtained using a dual energy X-ray absorptiometry (DXA), is the best indicator for predicting pertrochanteric fractures 11 . The mean force required to cause a pertrochanteric fracture is 3107+/−1066 N, however this value was arrived at, without considering other factors such as fall biomechanics and concomitantly acting muscular forces around the hip joint 11 .…”
Section: Discussionmentioning
confidence: 99%
“… 4 Many anatomical indications have been identified as the factors affecting the strength of the proximal femur, in which the bone mineral density of femoral neck is found to be significantly related to the strength of the proximal femur, 5 , 6 , 7 , 8 including the BMD measured by DXA and the densitometric variables measured by QCT. 9 In addition, the geometric variables measured by QCT, 9 the volumetric BMD (vBMD), cross‐sectional area, cortical thickness and large cortical bone hole of tibia, 10 the femoral neck cortical thickness and trabecular bone volume fraction, 11 the total cortical porosity, 12 the diameter of femoral neck, 13 the trochanteric cortical area, femoral neck width, 14 the femoral neck length, femoral head diameter, 15 and the cortical thickness , 16 etc., are also considered as the influencing factors of the strength of the proximal femur. Besides BMD, the other factors mentioned above are very difficult to be altered via clinical intervention.…”
Section: Introductionmentioning
confidence: 99%